2022
DOI: 10.1029/2021jd035457
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐Season Evaluation of CO2 Weather in OCO‐2 MIP Models

Abstract: The ability of current global models to simulate the transport of CO 2 by mid-latitude, synopticscale weather systems (i.e., CO 2 weather) is important for inverse estimates of regional and global carbon budgets but remains unclear without comparisons to targeted measurements. Here, we evaluate ten models that participated in the Orbiting Carbon Observatory-2 model intercomparison project (OCO-2 MIP version 9) with intensive aircraft measurements collected from the Atmospheric Carbon Transport (ACT)-America mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 68 publications
(115 reference statements)
2
14
0
Order By: Relevance
“…Our results show that the overall OCO-2 v9 MIP models underestimate the seasonal amplitude of NEE across central and eastern US ecosystems, regardless of data source. These results are consistent with the results of other studies using ACT-America observations (Cui et al, 2021;Feng et al, 2021;Zhang et al, 2022) but independent 2021) and this study for summer, fall, and spring, while an opposite sign of the mean bias estimates for winter likely due to the underestimates of ABL in WRF simulations of Cui et al (2021). Zhang et al (2022) co-sampled the ACT-America data in the posterior CO 2 fields of the OCO-2 v9 MIP.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our results show that the overall OCO-2 v9 MIP models underestimate the seasonal amplitude of NEE across central and eastern US ecosystems, regardless of data source. These results are consistent with the results of other studies using ACT-America observations (Cui et al, 2021;Feng et al, 2021;Zhang et al, 2022) but independent 2021) and this study for summer, fall, and spring, while an opposite sign of the mean bias estimates for winter likely due to the underestimates of ABL in WRF simulations of Cui et al (2021). Zhang et al (2022) co-sampled the ACT-America data in the posterior CO 2 fields of the OCO-2 v9 MIP.…”
Section: Discussionsupporting
confidence: 92%
“…These results are consistent with the results of other studies using ACT-America observations (Cui et al, 2021;Feng et al, 2021;Zhang et al, 2022) but independent 2021) and this study for summer, fall, and spring, while an opposite sign of the mean bias estimates for winter likely due to the underestimates of ABL in WRF simulations of Cui et al (2021). Zhang et al (2022) co-sampled the ACT-America data in the posterior CO 2 fields of the OCO-2 v9 MIP. They found seasonal model-data mismatch patterns in boundary layer CO 2 from the OCO-2 v9 MIP which are largely consistent with an underestimate in seasonal NEE magnitudes.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Using airborne in situ measurements of CO 2 fields obtained during the ACT-America RFs, Gerken et al (2021) exploited the performance of both mesoscale (WRF-Chem) and global scale (CT) models using identical surface fluxes and found reasonable agreement with observations in all four seasons. Additionally, for frontal RFs, Zhang et al (2022) also found that OCO-2 MIP models were capable of simulating observed CO 2 frontal contrasts with varying degrees of success in summer and spring, and frequent underestimation of frontal contrasts in winter and autumn.…”
Section: Overall Model-data Intercomparisonmentioning
confidence: 80%